PENGARUH EKSTRAKURIKULER ROHIS TERHADAP KARAKTER PERCAYA DIRI PESERTA DIDIK DI SMA NEGERI 2 PALEMBANG - Dzaky, Athaullah; Emil El Faisal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the influence of students' participation in Islamic Spiritual Extracurricular activities (Rohis) on the formation of confident character in SMA Negeri 2 Palembang. The research uses a quantitative approach with the research subject, namely students who actively participate in Rohis' extracurricular activities. The sampling technique used is purposive sampling with a saturated sampling method, so that all members of the population totaling 80 students are used as research samples. Data collection was carried out using a questionnaire instrument in the form of a Likert scale that has gone through validity and reliability tests to ensure the accuracy and consistency of the data. Data analysis was carried out using linear regression techniques. The results of the study show that Rohis extracurricular activities have a significant effect on the confident character of students, This finding indicates that Rohis extracurricular not only functions as a means of religious coaching, but also has a real contribution in strengthening the confident character of students.